Analysis of the Metabolites of Indole Degraded by an Isolated Acinetobacter pittii L1. (13th December 2017) - Yang, Zuoyi; Zhou, Junhui; Xu, Yanbin; Zhang, Yaping; Luo, Haien; Chang, KenLin; Wang, Yujie
Abstract : Indole and its derivatives are typical nitrogen heterocyclic compounds and have been of immense concern since they are known for the risk of their toxic, recalcitrant, and carcinogenic properties for human and ecological environment. In this study, a Gram-negative bacterial strain of eliminating indole was isolated from a coking wastewater. The strain was confirmed as Acinetobacter pittii L1 based on the physiological and biochemical characterization and 16S ribosomal DNA (rDNA) gene sequence homology. 400 mg/L indole could be completely removed within 48 h by the strain on the optimum condition of 37°C, pH 7.4, and 150 rpm. The organic nitrogen was converted to NH3 -N and then to N O 3 - and the organic carbon was partially transferred to CO2 during the indole biodegradation. The metabolic pathways were proposed to explain the indole degradation based on the liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis of indigo, 4-(3-Hydroxy-1H-pyrrol-2-yl)-2-oxo-but-3-enoic acid, and isatin. The toxicity of the biodegradation products was evaluated using the Microtox test, which revealed that the metabolites were more toxic than indole. Our research holds promise for the potential application of Acinetobacter pittii L1 for NHCs degradation, production of indigoids, and soil remediation as well as treatment of indole containing wastewater.